Guideline for Local’s Participation in Forest Product Areas at Champasak Province, Lao People’s Democratic Republic - Thongsavanh, Bounyadeth (Journal for Developing the Social and Community, 2019)
This research uses mixed-methods with the objective of research to 1) To study the problems and the establishment factors, to perform the obligations, roles, rights and responsibilities of the protection of the forest production 2) to study the opinions of the relevant sectors at the central and local levels in the protection of sustainable produce forests and 3) to study development approaches Establish practices in the protection of forests, sustainable production The target group by interviewing 14 people for government representatives, public sector representatives and private sector representatives by means of specific methods and sample groups of 301 persons. Determine the sample size according to Taro Yamane method. The sample error is equal to. 05 Tools used in Collection is a semi-structured interview. The statistics used in data analysis are frequency, percentage, mean. Standard deviation and content analysis, Findings of the study revealed as follows : Conditions, problems and factors of establishment, implementation of obligations, roles, rights, duties and responsibilities of forest protection, sustainable production by participation of people in Champasak District, Lao PDR. Regulations for each district to be enforced are still in operation and have not yet been achieved. Because people do not have knowledge and understanding such as forest allocation, substitution and utilization Smuggling, deforestation, and forest encroachment for land possession Lack of personnel to present performance and lack of attention of staff and other agencies The opinions of the relevant sectors at the central and local levels in the protection of sustainable produce Much The efficiency of joining the government in the protection of forests, production and conservation found that the efficiency of participation in the government in the protection of forests, production and overall preservation was at a moderate level. And participation in the protection of sustainable forest production, found that people participate in the protection of forests, producing sustainable products at a very good level. Guidelines for the development of practices in the protection of sustainable forest production found that suggestions on ways to develop public participation in the protection of sustainable produce forests should encourage youth to have consciousness and know about environmental conservation. There should be a promotion of the forest productive community of ecotourism for the promotion of public support for the benefits of environmental conservation, should encourage people to play a role in forest conservation activities. Much Should encourage all people and staff to participate in conservation, protection of forest produce There should be more public relations about forest protection production. Should create morale Encouragement for a complete forest protection zone Should be promoted Support training for knowledge on forest protection production Thoroughly and the operation or activities.